Antidepressant-like effect of low dose ketamine and scopolamine co-treatment in mice. (4th May 2016) - Petryshen, Tracey L.; Lewis, Michael C.; Dennehy, Kelly A.; Garza, Jacob C.; Fava, Maurizio
Highlights: Low dose ketamine (3 mg/kg) or scopolamine (0.1 mg/kg) is ineffective in the mouse FST. Co-treatment with subeffective doses of both drugs has an antidepressant-like effect. Low dose ketamine and scopolamine co-treatment may be effective for human depression. Abstract: Current medications for depression typically require weeks of treatment before significant clinical improvement is observed, and are only effective in a relatively small subset of patients. Recent human clinical studies have demonstrated that ketamine, an NMDA receptor antagonist, and scopolamine, a muscarinic acetylcholine receptor antagonist, produce rapid antidepressant responses within hours of administration, and are effective in treatment-resistant patients. We hypothesize that efficacy and tolerability may be improved by combining lower doses of both drugs in the treatment of depression. We therefore conducted a preclinical study in mice to assess whether co-treatment of low doses of scopolamine and ketamine that alone are ineffective has antidepressant-like effects in the forced swim test (FST), an assay with predictive validity for antidepressant drugs. Whereas single administration of ketamine (3 mg/kg intraperitoneal [i.p.]) or scopolamine (0.1 mg/kg i.p.) did not reduce immobility time in the FST, co-administration of both drugs at these doses significantly reduced immobility time by 45% compared to vehicle treated controls. These results suggest that the combination of subeffective doses of ketamine and scopolamine may prove efficacious for the treatment of depression and should be evaluated in human clinical trials.